Memorial of War, Memorial of Hope: Contemplating the creation, destruction, and re-creation of Fred Ross' mural The Destruction of War/Rebuilding the World Through Education, 1948,1954, and 2011 - Niergarth, Kirk (Labour / Le Travail, 2013)
The article is an extensive commentary on the history and significance of the mural, "The Destruction of War/Rebuilding the World Through Education," by Fred Ross. The mural was painted in the late 1940s at Fredericton High School in Fredericton, N.B. Removed in the 1950s, it was subsequently lost. A recreated version of the mural was installed at the University of New Brunswick in 2011.
Keywords: COLD War; 1945-1989; History; LOST works of art; MURAL painting & decoration – 20th century; New Brunswick; ROSS; Fred; WORLD War; 1939-1945 – Art & the war